Memory, war, and trauma - Hunt, Nigel C., 1963- (Cambridge, UK : Cambridge University Press, 2010)
'Many millions of people are affected by the trauma of war. Psychologists have a good understanding of how experiences of war impact on memory but the significance of external environmental influences is often disregarded. Memory, War and Trauma focuses on our understanding of the psychosocial impact of war in its broadest sense. Nigel C. Hunt argues that, in order to understand war trauma, it is critical to develop an understanding not only of the individual perspective but also of how societal and cultural factors impact on the outcome of an individual's experience. This is a compelling book which helps demonstrate why some people suffer from post-traumatic stress when other people don't, and how narrative understanding is important to the healing process. Its multi-disciplinary perspective will enable a deeper understanding of both individual traumatic stress and the structures of memory'--Provided by publisher.
Includes bibliographical references and index.
Keywords: War and society; War -- Psychological aspects; Post-traumatic stress disorder